Identification of gene function by cyclical packaging rescue of retroviral cDNA libraries - Bhattacharya, Deepta (National Academy of Sciences, 2002)
Genes regulating responses in mammalian cells are often difficult to identify by functional cloning strategies limited to a single round of selection. Here we describe a strategy, cyclical packaging rescue (CPR), which allows rapid recovery and retransmission of retroviral cDNA libraries. CPR can be used not only with immortalized cell lines such as fibroblasts and Jurkat T cells, but also with primary B lymphocytes, which can be maintained only in short-term cultures. CPR allows for multiple rounds of selection and enrichment to identify cDNAs regulating responses in mammalian cells. Using CPR, five cDNAs were functionally cloned, which conferred protection against tumor necrosis factor α (TNFα)-induced apoptosis in RelA(−/−) fibroblasts. Three of the genes, RelA, cellular FLICE-like inhibitory protein (c-FLIP), and a dominant-negative mutant of TNF receptor 1 arising through CPR afforded strong protection against apoptosis. Two of the genes identified, Dbs and Fas-associated death domain protein (FADD), previously identified as a proapoptotic molecule, afforded partial protection against TNFα-induced apoptosis. These results suggest that CPR is a versatile method that permits functional identification of both wild-type and dominant-negative gene products that regulate cellular responses.